Countdown 1960 the behind-the-scenes story of the 312 days that changed America's politics forever - Wallace, Chris; Weiss, Mitch (Dutton, 2024)
"It's January 2, 1960: the day that Massachusetts Senator John F. Kennedy declared his candidacy; and with this opening scene, Chris Wallace offers readers a front-row seat to history. From the challenge of primary battles in a nation that had never elected a Catholic president, to the intense machinations of the national conventions--where JFK chose Lyndon B. Johnson as his running mate over the impassioned objections of his brother Bobby--this is a nonfiction political thriller filled with intrigue, cinematic action, and fresh reporting. Like with many popular histories, readers will be familiar with the story, but few will know the behind-the-scenes details, told here with gripping effect."
Keywords: Kennedy, John F. -- 1917-1963; USA -- Präsident; Geschichte 1960; Präsidentenwahl; Wahlkampf; Presidents / United States / Election / 1960; Kennedy, John F. / (John Fitzgerald) / 1917-1963; Political campaigns / United States / History / 20th century; Campaign debates / United States / History / 20th century; Television in politics / United States / History / 20th century; Press and politics / United States / History / 20th century; Mass media / Political aspects / United States / History / 20th century; United States / Politics and government / 1945-1989; United States / History / 20th century; Nineteen sixties; Années soixante (Vingtième siècle); États-Unis / Politique et gouvernement / 1945-1989; États-Unis / Histoire / 20e siècle; Élections / Débats / États-Unis / Histoire / 20e siècle; Presidents / United States / Election; Presidential candidates / United States / Biography; Television and politics / United States; Press and politics / United States; Mass media / Political aspects; United States / Politics and government; Biography; Informational works; Biographies; Documents d'information